AVALIAÇÃO DE DANOS NO DNA E DE PRODUÇÃO DE RADICAIS LIVRES EM TRABALHADORES RURAIS - SANTOS, GREICE F. F. D.; ROCHA, JOÃO B. T. D.; BELLINASO, MARIA D. L.; GOETTEMS, PAULINE B.; GUECHEVA, TEMENOUGA N. (Salão do Conhecimento, 2013)
Resumo